The Impact of Gen Z Led TikTok Live Streaming on MSMEs' Sales Performance - Carollina, Nona; Daryono (Journal Economic Business Innovation, 2025)
Purpose: The purpose of this study is to investigate the mechanism through which TikTok live streaming conducted by Gen Z always enhances purchase intention toward MSME products, in which customer engagement serves as a significant mediator.Method: The quantitative data were obtained through online questionnaires from Gen Z Type TikTok MSME loggers, and processed with SPSS 28 with regression and mediation test results.Findings: An analysis of the results reveals that interactivity, authenticity, and entertainment enhance customer engagement in live streaming. Even more importantly, customer engagement completely mediates the relationship between these live streaming characteristics and purchase intention. The results showcase that the interaction features are not directly related to the intention to purchase but instead through the motivation they generate for psychological interaction, which then drives consumers to make a purchase; thereby providing a critical account of the adoption of live streaming commerce.Novelty: One full mediator customer engagement that this research recognizes in the TikTok live streaming context, without which our results are not possible (for Gen Z and MSMEs). It builds upon the Stimulus-Organism-Response framework by identifying the psychological process that bridges the gap between live streaming attributes and commercial outcomes with modes beyond direct-effect relationships.Implications: Thanks to this study, we offer important implications for both MSMEs and marketers because through live streaming commerce, firms should not sell directly to customers but build genuine customer engagement via interactivity, authenticity, and entertainment so that it plays the role of an enabler to better digital marketing strategies.